ANALYSIS OF ADOLESCENT COMPLIANCE FACTORS IMPLEMENTING THE COVID-19 HEALTH PROTOCOL IN NORTH TERNATE HIGH SCHOOL IN 2021 - Mirnawati Hi Hamjah; Pradnya Paramita; Tati Nuryati (Jurnal Inovasi Penelitian, 2022)
COVID-19 continues to develop, adolescents with confirmed COVID-19 are often asymptomatic. Another study showed that 81.9% of people aged 20 years and under did not show symptoms after being infected with the SARS-cov2 virus. Efforts to prevent the spread are by complying with the health protocols to prevent the spread of COVID-19 to help stop the spread of the COVID-19 virus. This study aims to determine the factors that influence adolescent compliance in the application of health protocols to prevent the spread of COVID-19 in SMA in North Ternate District based on health belief model (HBM). This study uses a quantitative method with a design cross sectional and uses a voluntary sampling technique. The study was conducted in July 2021. Of the 185 respondents who complied with the health protocol, 120 (64.9%) were teenagers. The results of the analysis, multivariate showed that the most dominant variable associated with protocol compliance was self-confidence {OR=2,505;95% CI (1,2-4,9) ; p = 0,009}